Sekularisme Radikalisme dan Terorisme dalam Pandangan Islam - Rosalia, Ai Ela; Himati Nur Azkiyah, Melani; Najmul Umam, Muhammad Mufti (CV Kalimasada Group, 2025)
This study examines the relationship between secularism, radicalism, and terrorism in the context of security and religious freedom in Indonesia. Extreme secularism can fuel radicalism, while radicalism can lead to terrorism. This qualitative research analyzes primary and secondary data sources. The findings indicate that secularism, radicalism, and terrorism significantly impact security and religious freedom. Effective prevention and countermeasures strategies are necessary. This research contributes to a deeper understanding of the relationship between secularism, radicalism, and terrorism and their implications for security and religious.